Peran Rumah Tahfidz Tadzkia Di Kelurahan Tanjung Sari Dalam Meningkatkan Pembelajaran Al-Qur’an Anak Dan Remaja - Anggriani, Putri; Naimi, Nadlrah (Journal of Community Sustainability, 2026)
This study aims to describe the role of Rumah Tahfidz Tadzkia in Tanjung Sari Village, Medan Selayang District, Medan City in improving Qur’anic learning among children and adolescents. The research employed a qualitative descriptive method, with data collected through observation, interviews, and documentation during the Community Service Program (KKN) conducted from September 1-13, 2025. The results show that Rumah Tahfidz Tadzkia plays a crucial role in shaping Quranic – oriented generations through the implementation of talaqqi, tikrar and muroja’ah learning methods. The learning process not only focuses on reading and memorizing skills but also emphasizes the cultivation of moral values and daily discipline. Supporting factors for the success of the program include community participation, innovative teaching methods, and the active guidance of instructors. The study concludes that Rumah Tahfidz Tadzkia serves as an effective non – formal educational institution in fostering spirituality, morality, and love for the Qur’an among children and adolescents in urban enviroments.